Ultrathin Co3O4 nanofilm as an efficient bifunctional catalyst for oxygen evolution and reduction reaction in rechargeable zinc–air batteries. Issue 25 (13th June 2017) - He, Yu; Zhang, Jinfeng; He, Guowei; Han, Xiaopeng; Zheng, Xuerong; Zhong, Cheng; Hu, Wenbin; Deng, Yida
Abstract : Two-dimensional nanocatalysts with a large specific surface area and efficient charge conductivity are promising candidates for catalyzing the oxygen evolution reaction and oxygen reduction reaction. Abstract : Two-dimensional (2D) nanocatalysts with a large specific surface area and efficient charge conductivity are promising candidates for catalyzing the sluggish oxygen evolution reaction (OER) and oxygen reduction reaction (ORR), which are at the heart of various electrochemical energy conversion and storage technologies. Here, we report the synthesis of an ultrathin Co3 O4 nanofilm with a thickness of nearly 1.8 nm via a surfactant- and template-free facile hydrothermal route. The proposed synthesis strategy can be extended to the preparation of 2D Ni x Co3− x O4 and Fe x Co3− x O4 nanostructures. The synthesized Co3 O4 nanofilm exhibited bifunctional activity that was superior to that of the counterpart Co3 O4 nanoparticles, including a lower overpotential and higher reduction and evolution current densities, and demonstrated faster catalytic kinetics over the 2D nanofilm surface. In comparison with precious metal-based catalysts, to achieve an OER current density of 40 mA cm −2 the overpotential of the nanofilm (461 mV) was lower than that of RuO2 (526 mV), whereas the ORR on the nanofilm proceeded via a dominant 4e − transfer mechanism, which is similar to that of commercial carbon-supported Pt (Pt/C). The Co3 O4 nanofilm enabled the assembly of rechargeable Zn–air batteries with a lower overpotential (0.72 V), higher round-trip efficiency (62.7%), and a longer cycle lifetime (175 cycles). The remarkable bifunctional activity contributes to an increase in the number of electrochemically active sites, a large interfacial contact area with the electrolyte, and the enrichment of Co 3+ ions on the surface, which facilitates the adsorption and activation of oxygen-containing species. This study should shed light on the future development of new electroactive materials with optimized 2D nanostructures to enhance the overall bifunctional ORR/OER performance of rechargeable metal–air batteries.